Analisis Kemampuan Memecahkan Masalah Matematika Materi Debit Pada Kelas V Sekolah Dasar - Lestari, Vitta Putri; Saputro, Bagus Ardi; Sukamto, Sukamto (EduBasic Journal: Jurnal Pendidikan Dasar, 2020)
Mathematical problem solving is a method used to solve knowledge and ability problems related to calculation problems, both personal problems and group problems in everyday life. This research was conducted to determine how the ability of students in solving math problems in elementary schools on discharge material using tests. This research was a type of research that uses qualitative methods with descriptive types, where each result of this analysis will be more accurately and clearly expressed about the problem-solving abilities of students in solving problems. The subjects were 5 students of fifth grade of elementary school. Data collection was carried out through questionnaires, observation, documentation, and tests of mathematical problem-solving abilities as well as interview guides. This research showed that 0% of students experience errors at the question reading stage. 20% of students indicate the error lies in understanding the problem. 16% of students indicated the location of the error in the transformation problem. 24% of students showed the location of the error in the numeracy process skills and the biggest error was writing the final answer by 80%. From this study, there were 1 student who scored below the minimum score, 4 students had exceeded the predetermined standard limit for mathematics lessons. Based on this research, it can find out the locations of the students' mistakes so that it provides instructions for the teacher where the teacher can deploy effective teaching strategies to overcome them.